Edukasi Manajemen Kecemasan pada Pasien Pre-Operasi Seksio Caesarea - Achmad Zainullah; Fransi Arsani (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Preoperative anxiety in patients undergoing cesarean section is a common condition that can negatively impact both physical and psychological well-being before delivery. Anxiety management education is a crucial strategy to help patients manage stress, enhance mental preparedness, and reduce the risk of complications caused by excessive anxiety. This study aims to evaluate the effectiveness of anxiety management education in reducing preoperative anxiety levels in cesarean section patients. The method used involves an educational intervention through a cognitive-based and relaxation approach, including breathing techniques and preoperative counseling. The results indicate that this education significantly reduces patients' anxiety levels, as evidenced by the difference in scores before and after the intervention. Therefore, anxiety management education programs should be implemented as part of maternal healthcare services to improve maternal well-being before undergoing a cesarean section.